Polysplenia Syndrome and the Development of Heart Failure due to Associated Congenital Heart Defect - Valerie Van Ballaer; Pieter Meersman; Nico Hustings (Journal of the Belgian Society of Radiology)
Key message: Patients with polysplenia syndrome can develop pulmonary hypertension and heart failure due to underlying congenital heart disease, underscoring the need for early recognition and intervention to prevent further progression of the condition.